Weather Impact on Nursery Diseases of Mango Saplings in Bangladesh - Khan, M. A. H.; Hossain, I.; Chowdhury, M. S. M.; Ahmad, M. U. (International Journal of Applied Sciences and Biotechnology, 2015)
The study was carried out during the period of July 2010 to April 2012 to find out the effect of weather prevalence of seedling diseases ofmango in different areas of Bangladesh. The locations were Mymensingh Dinajpur, Rajshahi and Khagrachari. Altogether 12 nurseries in fourdistricts of Bangladesh were surveyed and mango seedling diseases were recorded. Incidence and severity of important seedling diseases ofhas been studied under different geographical locations (viz. Mymensingh, Dinajpur, Rajshahi and Khagrachari) of Bangladesh. The effects oftemperature, rainfall, and relative humidity on the incidence and severity of noted diseases were observed the aforesaid locations of Bangladesh.The studied diseases were anthracnose, leaf spot, red rust, powdery mildew, scab, bacterial leaf blight and malformation of mango seedlings.The graphs of weather parameters and incidence and severity of diseases were performed to determine the relationship between differentcomponents of climatic factor and seedling diseases of mango.DOI: http://dx.doi.org/10.3126/ijasbt.v3i1.11846   Int J Appl Sci Biotechnol, Vol. 3(1): 42-49